Answer:72
Step-by-step explanation:because idk
The expanded form of 0.917 is
0.+.900+.10+.7
On simplifying the expression 13.8+ (-11.5) , we get 2.3 . And additions
13.8 + (-11.5) and (-13.8) + 11.5 are numbers will same value and opposite sign.
<h3>What are rules for adding a positive and a negative number?</h3>
For adding a negative and a positive number, use the sign of the larger number and subtract.
For example: (–8) + 2 = -6
Given that we have to solve 13.8 + (-11.5) = 13.8-11.5 (we subtract smaller no from larger and will use the sign of lager number that is + here)
13.8+(-11.5) = 13.8-11.5 =2.3
13.8+(-11.5) simply means that 13.8 -11.5 which is subtraction of 11.5 from 13.8
but (-13.8) + 11.5 = -13.8 +11.5 = -( 13.8 -11.5) [taking -1 common from the expression]
Therefore , -13.8 + 11.5 has same value as 13.8- 11.5 but opposite in sign.
Learn, More about addition of numbers from here:'
brainly.com/question/14092461
#SPJ1
9:
-q^2 - r^2 + 3s
-9^2 - -6^2 + 3(-20)
-9^2 = -9 * -9 = 81
81 - -6^2 + 3(-20)
-6^2 = -6 * -6 = 36
81 - 36 + 3(-20)
3(-20) = -60
81 - 36 + -60
81 + 36 = 117
117 + (-60)
117 - 60= 57
57
10:
3| x + y |^2 - (xy)^2
3| 3 + -5 |^2 - (3-5)^2
(3-5) = 2
3| 3 + -5 |^2 - 2^2
|3 + -5| = 8
3|8|^2 - 2^2
8 * 8 = 64
3(64) - 2^2
2^2 = 2*2 = 4
3(64) - 4
3*64 = 192
192 - 4 = 188
188
11:
2x^2 - 5xy - y^3
2(-3)^2 - 5(-3-2) - -2^3
(-3-2) = -5
2(-3)^2 - 5(-5) - -2^3
-3^2 = -3 * -3 = -9
2(-9) - 5(-5) - -2^3
2^3 = 2 * 2 * 2 = 8
2(-9) - 5(-5) - 8
18 - 5(-5) - 8
5(-5) = -25
18 - (-25) - 8
18 + 25 - 8
18 + 25 = 43
43 - 8 = 35
35
12: -a^2 + 7b^4 -2c^3
—4^2 + 7(-2)^4 - 2(-3)^3
4^2 + 7(-2)^4 - 2(-3)^3
4 * 4 = 16
16 + 7(-2)^4 - 2(-3)^3
-2 * -2 * -2 * -2 = 16
16 + 7(16) - 2(-3)^3
-3 * -3 * -3 = -27
16 + 7(16) - 2(-27)
7 * 16 = 112
16 + 112 - 2(-27)
2 * -27 = -54
16 + 112 - -54
16 + 112 + 54
112 + 16 = 128
128 + 54 = 182
182
2 divides both numbers, so divide both numbers by 2 to get 3 and 7. These are relatively prime, so 2 is the gcd. The lcm is 6*14/2=42.